’Manfalouti’s Style in his book ‘Al- Nazarat - Inosa, Widraogo; bin Abdul Halim, Tho Al Azhan (Journal of Humanities & Social Sciences, 2019)
Mustafa Lutfi Manfalouti, a social reform writer, has many articles and books. One of the writer’s famous books is ‘Al- nazarat’ in which he dealt with various topics in the criticism of several aspects of life. In this book, the author focused on reality, imagination, and illustrations because he is critical in the choice of adjectives and their nouns. Thus, the author provides detailed descriptions and uses narrative techniques that express his full coverage of events such as al- ru’yah min khalf, al- ru’yah al- Ilahiyyah, and al- ru’yah ma’. The author relies on the choice of feminine gender for expressions in tragic stories, focusing on pessimism and criticism towards painful social realities, using various stories on his extensive historical background, and establishing the reader's principle of contentment and self- respect. The author also addresses the people concerned in most of his reformist speeches, believing that they have original and good qualities. This study describes Manfalouti’s style as observed by the researcher through reading the various stories in the author’s books and articles. The themes are briefly described and categorized according to the appropriate contexts.
Keywords: al-Manfalouti; book of looks; stories and essays; style; description; truth; fiction